Taxonomic and nomenclatural adjustments in Mimosa sect. Mimosa ser. Mimosa Barneby (Fabaceae, Caesalpinioideae) - Mendes, Thainara Policarpo [UNESP]; Silva, Marcos José Da [UNESP] (Magnolia Press, 2024)
The taxonomic revision of Mimosa sect. Mimosa ser. Mimosa subser. Polycephalae resulting from the analysis of protologs and the study of approximately 450 collections, including all types, in addition to collections and observations of populations in the field, led us to identify problems of typification, concept, and circumscription for some species directing us to stablish 13 synonymizations, 11 lectotypifications, seven of which were second step, as well as propose the ranking of five varieties to the species level. From this work, the ser. Polycephalae now comprises 34 species.
Keywords: Brazilian flora; mimosoid clade; Nomenclature; typus